Fabrication And Characterization Of Poly (L-Lactic Acid) (Plla) Blends And Pllaikenaf Fiber Composites - Eawwiboonthanakit, Netnapa (2014)
Environmental impacts are the main global concem which induce to incremental awareness on the replacement of conventional plastic materials by biodegradable plastic e.g. Poly (L-Iactic acid) (PLLA). Investigations on mechanical and thermal properties of PLLA blends and PLLA/kenaf fiber composites by internal mixing were observed in this study. Properties of PLLA blended with polymer additives; carboxyl-terminated butadiene acrylonitrile (CTBN), acrylonitrile butadiene styrene (ABS) and poly (lactic acid) (PLA) microsphere at various blend ratios (10010, 98/2, 96/4, 94/6 and 92/8 wt%) are observed in the first part. It was found that PLLA/PLA microsphere blend at 92/8 blend ratio presented higher mechanical, thermal and melt now index properties with resulting of fibril formation in the microstructure compared to other blends systems. Effects of fiber surface modification and fiber loading on the mechanical and thermal properties of kenaf fiber (KF) in PLLAIPLA microsphere/KF composites were investigated in second part of study. Addition of 4 wt% of treated KF (T-KF) in the composite illustrated higher flexural strength and easy to process compared to composite with 30 wt% of T -KF content.